Artificial Brain Using Wetware Technology and Fuzzy Logic - Daina, KK; Sindhura, D; Vinod kumar, R; Dhanalakshmi, HB (International Journal of Computer Sciences and Engineering, 2025)
The Blue Brain Project is that the initial created comprehensive attempt to reverse engineer the brain of mammalian, so through elaborated simulations the perform of brain are often understood. BLUE BRAIN is that the name of the world’s initial virtual brain which suggests, a machine that may perform as human brain. Today, scientists square measure in analysis to form a synthetic brain that may suppose, respond, take call, and store something in memory. the most aim of this analysis is to transfer human brain into machine. so man will suppose and take call with none effort. This technology is often used for the event of human society.